Effect of prebiotic oligosaccharides on gut health and performance of chickens - Flaujac Lafontaine, Geraldine M (2020)
Interest in prebiotics and their potential application for human and animal health is flourishing. Here, the effects of galacto-oligosaccharide (GOS) on the performance and health of chickens, with the potential for human applications was evaluated. Following a review of the poultry meat industry from economic and animal welfare standpoints, the outcomes of GOS feedstuff on the gut health and immune function of broiler chickens were evaluated. First, the effects of in-feed inclusion of GOS on broiler chicken performance and intestinal immune status were assessed in the absence of intestinal challenge. The GOS diet was shown to modulate the juvenile gut microbiome and innate immunity to increase weight gain and reduce the cumulative feed conversion ratio. GOS-associated activation of mucosal Th17 immune response at a young age was accompanied with a shift in the microbiota composition promoting one member of autochthonous Lactobacillus spp at the expense of another. The cecal abundance of immuno-modulatory L. johnsonii was shown to increase on the GOS diet and positively correlate with bird growth weight at 35 days of age. The impact of GOS was further assessed upon bacterial challenge with the foodborne pathogen Campylobacter jejuni. C. jejuni challenge effects on birds maintained on a normal diet were first characterised. The study identified age-dependent differences in the kinetics of cecal colonisation, microbiome compositional shifts, and Th 17 induced intestinal immune responses. Upon C. jejuni challenge, broilers maintained on a GOS diet continued to exhibit the growth advantage. Despite successful cecal colonisation by C. jejuni, GOS selectively induced microbiota shifts associated with Th17 induction. Due to limited evidence of the direct impact of dietary fibres on the intestinal barrier, the effects of GOS and fructo-oligosaccharides (FOS) on the transcriptome of polarised human colonic epithelial cells were evaluated. Both oligosaccharides improved epithelial tight junctions as indicated by increases in trans-epithelial resistance. However, the effects of FOS on the transcriptome were reduced when compared to GOS. Our strategy produced a comprehensive curated gene expression database that will permit further work to link gene expression signatures of cultured cells to their mode of action, thus potentially facilitating product choices in human or animal intervention studies.